Pengaruh Kelelahan Emosional terhadap Kepuasan Kerja dengan Employee Commitment sebagai Variabel Moderating Selama Masa Pandemi Covid-19 - Syahla Fitri; Sri Suwarsi (UNISBA Press, 2022)
Abstract. The Covid-19 pandemic has brought many changes in various work sectors, especially the education sector which has an impact on human resources in it. Human resources who are able to maintain their emotions are something that can encourage job satisfaction. To survive in an organization, especially during the covid19 pandemic, it is necessary to hace a commitment that appears in these human resources that can increase job satisfaction. Therefore, the purpose of this study was to examine emotional exhaustion on job satisfaction with employee commitment as a moderating variable. In this study, the research design used is a quantitative study using the entire population without having to draw a research sample as a unit of observation called the census technique. Research data collected by interview method and analyzed descriptively and multiple linear regression. The results of this study show that the variable of emotional exhaustion with descriptive analysis results produces an average score of 279.07 which is included in the sufficient category. The job satisfaction variable with the results of descriptive analysis resulted in average score of 258.42 which was included in the sufficients category, and employee commitment with the results of the descriptive analysis of 328.66 which was included in the high category. The next results is that there is an effect of emotional exhaustion on job satisfaction by 8.6% and after employee commitment is included there is a decrease of 2.1% which can be interpreted that employee commitment is a moderating variable with an effect of 6.5%. This shows that employee commitment has a positive effect on the relationship between emotional exhaustion variables and job satisfaction variables.Keywords: Emotional Exhaustion, Job Satisfaction, Employee Commitment. Abstrak. Pandemi Covid-19 banyak membawa perubahan di berbagai sektor pekerjaan, khususnya sektor pendidikan yang berdampak pada sumber daya manusia didalamnya. Sumber daya manusia yang mampu menjaga emosionalnya merupakan suatu hal yang dapat mendorong kepuasan kerja. Untuk bertahan disuatu organisasi terlebih di masa pandemi covid-19, perlu adanya komitmen yang muncul dalam diri sumber daya manusia tersebut yang mampu meningkatkan kepuasan kerja. Oleh karena itu, tujuan dari penelitian ini untuk menguji kelelahan emosional terhadap kepuasan kerja dengan employee commitment sebagai variabel moderating. Dalam penelitian ini, rancangan penelitian yang digunakan adalah penelitian kuantitatif dengan menggunakan seluruh populasi tanpa harus menarik sampel penelitian sebagai unit observasi disebut sebagai teknik sensus. Data penelitian dikumpulkan dengan metode wawancara dan dianalisis secara deskriptif dan regresi linier berganda. Hasil dari penelitian ini menunjukan variabel kelelahan emosional denganhasil analisis deskriptif menghasilkan skor rata-rata 279.07 yang termasuk dalam kategori cukup. Variabel kepuasan kerja dengan hasil analisis deskriptif menghasilkan skor rata-rata sebesar 258.42 yang termasuk dalam kategori cukup, dan employee commitment dengan hasil analisis deskriptif sebesar 328.66 yang termasuk dalam kategori tinggi. Hasil selanjutnya yaitu terdapat pengaruh kelelahan emosional terhadap kepuasan kerja sebesar 8.6% dan setelah employee commitment dimasukkan terjadi penurunan sebesar 2.1% yang dapat diartikan bahwa employee commitment merupakan variabel moderating dengan pengaruh sebesar 6.5%. Hal ini menunjukkanbahwa employee commitment berpengaruh positif dalam hubungan antara variabel kelelahan emosional dan variabel kepuasan kerja.